Beyond economic growth goals: can foreign aid mitigate carbon dioxide emissions in developing countries? - Karim Barkat (17823665) (2024)
We provide novel and compelling evidence that foreign aid has significant mitigating impacts on carbon dioxide emissions in a comprehensive panel dataset of 127 developing countries from 1995 to 2019. This impact operates through a direct effect resulting from the adoption of green and eco-friendly investments and an indirect effect driven by economic growth. Moreover, we reveal that the effectiveness of foreign aid in reducing carbon dioxide emissions is contingent upon the country's income level. Specifically, foreign aid shows limited efficacy in curbing emissions in low-income countries, while its influence becomes substantial in middle-income countries. This result indicates that economic development plays a moderating effect in the aid – climate change nexus. Furthermore, the findings of this research are of paramount importance to donor and recipient countries emphasizing the role of governance and political stability in enhancing the effectiveness of aid in combatting climate change and identifying promising pathways for sustainable development. Other Information Published in: Journal of Cleaner Production License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jclepro.2024.143411